Osteoarthritis of knee joint - role of quadriceps exercises - Ansari, M.A.Q.; Asimuddin, M. (International Journal of Research in Medical Sciences, 2017)
Background: Osteoarthritis of knee joint is a common clinical condition among patients attending orthopaedics outpatient department. The role of quadriceps exercises in its management is not effectively stressed. Hence this study was carried out to assess the role of Quadriceps exercises in management of Osteoarthritis of Knee and reduce the morbidity associated with it. Methods: A total of one hundred patients in the age group of 40-65 years and suffering from mild to moderate Osteoarthritis of the knee joint were included in the study. Subjects were divided into two groups, Group I receiving drug therapy only and Group II receiving physiotherapy also, in the form of quadriceps exercises. Data was recorded on a proforma designed to assess symptomatic relief after two weeks. Results: Participants in group II with exercise program had improvements in physical function and symptom relief, decrease in knee pain and increase in range of motion, more than that of participants in group I. It was observed that majority of the study subjects, 39 (78%) had excellent result in group II, whereas 12 (24%) patients from group I had poor result. Conclusions: There is relationship between age, sex and quadriceps exercise with osteoarthritis of knee. Moderate quadriceps exercise is a safe and effective prevention and therapy for Osteoarthritis of knee.